ACC Deaminase-Positive Halophilic Bacterial Isolates With Multiple Plant Growth-Promoting Traits Improve the Growth and Yield of Chickpea (Cicer arietinum L.) Under Salinity Stress - Nagaraju, Yalavarthi; Mahadevaswamy,; Naik, Nagaraj M.; Gowdar, S. B.; Narayanarao, K.; Satyanarayanarao, K. (Frontiers in Agronomy, 2021)
In the current research study, a total of fifty halophilic bacterial isolates were screened for ACC deaminase activity of these six with the highest ACC deaminase activity were selected for an increase in chickpea yield under salinity. The ACC deaminase activity among the isolates was ranged between 0.12 to 3.56 mM α-KB mg-1 min-1. These six isolates and one reference strain from Agricultural College, Raichur, were used in a microcosm experiment during the rabi season of 2018. After 60 days of sowing, decreased rhizosphere pH and EC from 8.4 to 7.6 and 4.3 to 3.4, respectively, were reported in chickpea. Among the treatments, B. safensis inoculated plants showed a higher number of flowers (71 flowers/plant), pods (49.3 pods/plant), branches (33.3 branches/plant), as well as enhanced fresh weight (17.2 g/plant), and dry weight (8.1 g/plant). They were corroborated by improved nitrogen and phosphorous absorption of 71.5 and 43.5 percent, respectively, in B. safensis-treated plants. Based on the microcosm experimental findings, three cultures improving biometric and yield attributes were chosen for the field investigation. The field study was carried out at Agricultural Research Station, Ganagavathi, during Kharif 2019. The chickpea plants treated with the consortium (B. safensis, P. stutzeri, and S. xylosus) increased plants' superoxide dismutase and catalase activity by 258 and 196 %, respectively. In addition, an increase in Ascorbate peroxidase activity (0.41 μmol of ascorbate oxidized s-1 g-1 fw) in leaves and proline content was also recorded. The consortium (B. safensis, P. stutzeri, and S. xylosus) significantly increased nutrient uptake (N and P), the number of flowers, number of pods, and yield by 63.26, 39.03, 110, 59.96, and 17.56 % respectively in chickpeas. Finally, inoculation with a mixture of three isolates is an effective method for increasing chickpea production under osmotic stress.